2007
DOI: 10.1007/s00330-007-0586-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital mammography: what do we and what don’t we know?

Abstract: High-quality full-field digital mammography has been available now for several years and is increasingly used for both diagnostic and screening mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 75 publications
0
48
0
1
Order By: Relevance
“…The use of paramagnetic contrast medium [3,10] allows the study of breast mass vascularisation, allowing the investigation of the tumoral angiogenetic bed [11][12][13]. This finding forms the basis for lesion characterisation that is not therefore based on a morphological evaluation of the mass alone but above all on the qualitative and quantitative evaluation of its vascularisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of paramagnetic contrast medium [3,10] allows the study of breast mass vascularisation, allowing the investigation of the tumoral angiogenetic bed [11][12][13]. This finding forms the basis for lesion characterisation that is not therefore based on a morphological evaluation of the mass alone but above all on the qualitative and quantitative evaluation of its vascularisation.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside cytological and histological examinations, imaging techniques have always played a key role in diagnosing breast cancer and in the characterisation of nodular diseases of the breast that may pose a differential diagnosis. Among the breast imaging techniques commonly used, the role, advantages and limitations of mammography [2][3][4], ultrasound (US) and colour Doppler ultrasound [4][5][6][7][8][9] are well known and extensively described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…With additional projections this may be intercepted, thereby reducing false positive recalls [14]. Moreover, as an extra view, it is expected to contribute to the early detection of breast cancer [15,16]. Finally, low dose mammography images could be applied in post interventional mammography [17], such as marker or wire verification, or in high frequency surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to its ability to detect subtle abnormalities and microcalcifications that may represent early cancer [1,2] . There has been replacement of screen-film mammography (SFM) with full field digital mammography (FFDM) in many centres because of consistent image quality of digital images, ability to post-process digital images and improved storage and transmission capabilities [3] . A number of studies have been conducted to compare screen-film with digital mammography and results have shown that digital imaging is as good as SFM in population based screening practices [4][5][6][7][8] , although most of these studies rely on surrogate end points such as cancer detection rate, recall rate and tumour characteristics at diagnosis.…”
Section: Introductionmentioning
confidence: 99%